A polycarbonate composition, its preparation and use

CN121379092BActive Publication Date: 2026-10-27KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511667463.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2026-10-27
Estimated Expiration
2045-11-14

AI Technical Summary

Technical Problem

然而这些方法均存在一些问题,例如,结晶性聚合物本身较脆且与PC相容性差,合金的抗冲击性能会明显下降

Benefits of technology

本发明提供了一种聚碳酸酯组合物,所述聚碳酸酯组合物在保持了优异的力学性能与热变形温度的前提下,还显著提高了耐溶剂性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a polycarbonate composition, a preparation method and application thereof. The polycarbonate composition comprises the following components in parts by weight: 44-76 parts of polycarbonate resin, 24-56 parts of polyphenylene sulfone resin, 0.1-1 part of antioxidant and 0.1-1 part of lubricant. The weight average molecular weight of the polycarbonate resin is 15000-55000. The total water content of the polycarbonate resin and the polyphenylene sulfone resin as the raw materials of the polycarbonate composition is less than or equal to 0.1%. The antioxidant is a phosphite antioxidant. The thermal decomposition temperature of the lubricant is greater than or equal to 280 DEG C. The polycarbonate composition has good mechanical properties, a heat distortion temperature and solvent resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of engineering plastics, and more specifically, relates to a polycarbonate composition, its preparation method, and its application. Background Technology

[0002] The poor solvent resistance of polycarbonate resin is an inherent defect. This is because its molecular chain is relatively rigid, resulting in greater internal stress after molding. Furthermore, the loose molecular weight stacking facilitates solvent penetration and easily forms stress concentration points inside, which can then develop into cracks, leading to polycarbonate resin cracking.

[0003] Currently, the solvent resistance of polycarbonate resin is mainly improved through blending modification. The second component of the blend is usually a crystalline polymer (e.g., PET, PBT), an amorphous polymer with flexible segments (e.g., ABS, PVB), or nanofillers. However, these methods all have some problems. For example, crystalline polymers are brittle and have poor compatibility with PC, which significantly reduces the impact resistance of the alloy. Amorphous polymers with flexible segments often have poor heat resistance, and blending them with polycarbonate resin will significantly reduce its heat distortion temperature. The dispersion of nanofillers in the polycarbonate resin matrix is ​​difficult to control, and they may even agglomerate to form stress concentration points that induce cracking in the polycarbonate resin.

[0004] Therefore, improving the solvent resistance of polycarbonate resin systems while ensuring the mechanical and heat resistance properties of polycarbonate resins has become an urgent technical problem to be solved. Summary of the Invention

[0005] In view of the above-mentioned existing technical problems, the primary objective of the present invention is to provide a polycarbonate composition that, while maintaining excellent mechanical properties and a high heat distortion temperature, also significantly improves solvent resistance.

[0006] A second objective of this invention is to provide a method for preparing a polycarbonate composition.

[0007] A third objective of this invention is to provide an application of a polycarbonate composition in the fields of household appliances, consumer electronics, and medical devices.

[0008] The fourth object of the present invention is to provide a kitchen appliance or electrical product.

[0009] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention claims protection for a polycarbonate composition comprising, by weight, the following components: 44-76 parts polycarbonate resin, 24-56 parts polyphenylene sulfone resin, 0.1-1 parts antioxidant, and 0.1-1 parts lubricant; wherein the polycarbonate resin has a weight-average molecular weight of 15,000-55,000; the total water content of the polycarbonate resin and polyphenylene sulfone resin used in the preparation of the polycarbonate composition is ≤0.1%; the antioxidant is a phosphite antioxidant; and the lubricant has a thermal decomposition temperature ≥280℃.

[0010] In this invention, polyphenylene sulfone resin and polycarbonate resin are combined. Polyphenylene sulfone resin has an extremely stable aromatic ring backbone structure, highly inert sulfone groups, and highly stable ether bonds. This makes the composite system formed by combining it with polycarbonate resin difficult to be penetrated, swollen, or degraded by solvents, and it also exhibits excellent physical and mechanical properties. Furthermore, the inventors discovered that by controlling the water content of the raw materials, polycarbonate resin and polyphenylene sulfone resin, within a specific range, the hydrolysis reaction occurring at high temperatures during the combined preparation process can be reduced, thereby reducing chain scission of the polycarbonate resin and avoiding impact on the notched impact strength, heat distortion temperature, and solvent resistance of the polycarbonate composition. Furthermore, this invention found that phosphite antioxidants can capture free radicals (such as hydroperoxides) generated during the degradation of polycarbonate resin, inhibiting the degradation of polycarbonate resin and thus improving the performance of the polycarbonate composition. Using lubricants with high thermal decomposition temperatures can also reduce the frictional shear heat generated by the molecular chains of polycarbonate resin and polyphenylene sulfone resin during processing, further improving the processing thermal stability of the polycarbonate / polyphenylene sulfone resin composite system.

[0011] This invention combines polyphenylene sulfone resin and polycarbonate resin, controls the total water content of the raw materials polycarbonate resin and polyphenylene sulfone resin, and selects phosphite antioxidants and lubricants with high thermal decomposition temperatures. The resulting polycarbonate composition not only maintains excellent mechanical properties and high heat distortion temperature, but also significantly improves solvent resistance.

[0012] Specifically, the amount of polycarbonate resin can be 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, or any range of the above values; the present invention is not limited thereto. The amount of polyphenylene sulfone resin can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, or any range of the above values; the present invention is not limited thereto. The amount of antioxidant can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, or any range of the above values; the present invention is not limited thereto. The amount of lubricant can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, or any range of the above values; the present invention is not limited thereto.

[0013] Specifically, the total water content of the polycarbonate resin and polyphenylene sulfone resin used in the preparation of the polycarbonate composition is ≤0.1%. More specifically, the total water content of the polycarbonate resin and polyphenylene sulfone resin used in the preparation of the polycarbonate composition can range from 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or any range formed by the above values; the present invention is not limited thereto. Preferably, the total water content of the polycarbonate resin and polyphenylene sulfone resin used in the preparation of the polycarbonate composition is 0.02-0.1%; more preferably, the total water content is 0.0275-0.0875%. The total water content can be obtained by testing the water content of each of the polycarbonate resin and polyphenylene sulfone resin.

[0014] Specifically, in this invention, the polycarbonate resin accounts for no less than 43.1% of the mass percentage of the polycarbonate composition. Specifically, in this invention, the polyphenylene sulfone resin accounts for no less than 23.5% of the mass percentage of the polycarbonate composition.

[0015] Preferably, the phosphite antioxidant is selected from at least one of bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, and 3,9-bis(2,4-dicumylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosspiro[5.5]undecane.

[0016] Preferably, the melting point of the phosphite antioxidant is ≥200℃; more preferably, the melting point of the phosphite antioxidant is 225-260℃. Specifically, the melting point of the phosphite antioxidant is 234-250℃. This invention uses a high-melting-point phosphite antioxidant, which, during melt extrusion processing, can reduce the degradation of polycarbonate resin at higher processing temperatures, thereby improving the notched impact strength and solvent resistance of the polycarbonate composition.

[0017] Specifically, the melting point of the phosphite antioxidant can be 225℃, 230℃, 240℃, 245℃, 250℃, or any range formed by the above values, and the present invention is not limited thereto. Specifically, the test method for the melting point of the phosphite antioxidant is GB / T 19466.1-2004.

[0018] More preferably, the phosphite antioxidant is selected from bis(2,4-dicumylphenyl)pentaerythritol-diphosphite. Bis(2,4-dicumylphenyl)pentaerythritol-diphosphite has a high melting point and can effectively improve the notched impact strength, heat distortion temperature and solvent resistance of the polycarbonate composition.

[0019] Preferably, the lubricant is selected from at least one of pentaerythritol ester lubricants, stearate lubricants, paraffin lubricants, and amide lubricants. More preferably, the pentaerythritol ester lubricant is selected from at least one of pentaerythritol tetrastearate, pentaerythritol tetrapalmitate, pentaerythritol tetraoleate, and pentaerythritol tetralaurate.

[0020] Preferably, the weight-average molecular weight of the polyphenylene sulfone resin is 18,000-60,000. More preferably, the weight-average molecular weight of the polyphenylene sulfone resin is 20,000-59,000. More preferably, the weight-average molecular weight of the polyphenylene sulfone resin is 40,000-59,000. Specifically, the weight-average molecular weight of the polyphenylene sulfone resin can be 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, etc., or any range formed by the above values, and the present invention is not limited thereto. Specifically, the test method for the weight-average molecular weight of the polyphenylene sulfone resin is GB / T 36214.4-2018, the solvent is chloroform, and the weight-average molecular weight standard is polystyrene.

[0021] Preferably, the melt flow rate of the polyphenylene sulfone resin at 365°C and 10 kg is 20-50 g / 10 min. The melt flow rate of the polyphenylene sulfone resin at 365°C and 10 kg can be 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, or any range of the above values; the present invention is not limited thereto. Specifically, the test method for the melt flow rate of the polyphenylene sulfone resin is GB / T 3682.1-2018.

[0022] Preferably, the polycarbonate resin is a bisphenol A type polycarbonate resin.

[0023] Preferably, the weight-average molecular weight of the polycarbonate resin is 20,000-30,000. More preferably, the weight-average molecular weight of the polycarbonate resin is 20,000-24,000. Specifically, the weight-average molecular weight of the polycarbonate resin can be 20,000, 23,000, 25,000, 28,000, etc., or any range formed by the above values, and the present invention is not limited thereto. Specifically, the test method for the weight-average molecular weight of the polycarbonate resin is GB / T 36214.4-2018, the solvent is chloroform, and the weight-average molecular weight standard is polystyrene.

[0024] Preferably, the melt flow rate of the polycarbonate resin at 300°C and 1.2 kg is 3-40 g / 10 min. More preferably, the melt flow rate of the polycarbonate resin at 300°C and 1.2 kg is 10-20 g / 10 min. Specifically, the melt flow rate of the polycarbonate resin at 300°C and 1.2 kg can be 5 g / 10 min, 7 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, etc., or any range formed by the above values, and the present invention is not limited thereto. Specifically, the test method for the melt flow rate of the polycarbonate resin is GB / T 3682.1-2018.

[0025] Preferably, the thermal decomposition temperature of the lubricant is 290-350℃. Specifically, the thermal decomposition temperature of the lubricant is 300-330℃. More specifically, the thermal decomposition temperature of the lubricant can be 300℃, 305℃, 310℃, 315℃, 320℃, 325℃, 330℃, 335℃, 340℃, 345℃, etc., or any range formed by the above values; the present invention is not limited thereto. Specifically, the method for testing the melting point of the lubricant is GB / T 19466.1-2004.

[0026] Preferably, the water content of the polycarbonate resin is ≤0.1%; more preferably 0.02-0.1%; and / or the water content of the polyphenylene sulfone resin is ≤0.25%, more preferably 0.05-0.25%.

[0027] Specifically, the water content of the polycarbonate resin can be 0.02%, 0.04%, 0.08%, 0.1%, or any range formed by the above values, and the present invention is not limited thereto. Specifically, the test method for the water content of the polycarbonate resin is GB / T 9914.1-2013.

[0028] Specifically, the water content of the polyphenylene sulfone resin can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or any range formed by the above values; the present invention is not limited thereto. Specifically, the test method for the water content of the polyphenylene sulfone resin is GB / T 9914.1-2013.

[0029] Specifically, in some embodiments, polycarbonate resin or polyphenylene sulfone resin can be dried using conventional drying methods in the art to obtain polycarbonate resin or polyphenylene sulfone resin with the corresponding water content.

[0030] More specifically, in some embodiments, the polycarbonate resin is dried by forced air at a temperature of 110-130°C for 3-5 hours. More specifically, in some embodiments, the polyphenylene sulfone resin is dried by forced air at a temperature of 160-180°C for 3-7 hours.

[0031] Furthermore, this invention claims protection for a method for preparing a polycarbonate composition, wherein the raw materials of each component are mixed evenly, melt-extruded, and the polycarbonate composition is obtained.

[0032] Preferably, the melt extrusion temperature is 280-330°C. More preferably, the melt extrusion temperature is 300-320°C.

[0033] Preferably, a twin-screw extruder is used for extrusion. The length-to-diameter ratio of the twin-screw extruder is 40-50:1.

[0034] Preferably, the twin-screw extruder operates at a speed of 200-500 r / min. More preferably, the twin-screw extruder operates at a speed of 300-400 r / min.

[0035] Furthermore, this invention claims protection for the use of a polycarbonate composition in the fields of household appliances, consumer electronics, and medical devices.

[0036] Furthermore, the present invention claims protection for a kitchen appliance or electrical product prepared using the above-described polycarbonate composition.

[0037] More specifically, the specific application scenarios for kitchen appliances refer to household appliances that require prolonged contact with solvents such as grease and oil, such as refrigerator inner shelves, range hood casings, and toaster knobs. More specifically, electrical products include, but are not limited to, headphones, speakers, and smartwatch casings that require prolonged contact with skin, cleaning agents, and skincare products.

[0038] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a polycarbonate composition that, while maintaining excellent mechanical properties and heat distortion temperature, also significantly improves solvent resistance. Detailed Implementation

[0039] The present invention will be further described below with reference to the specification and specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in this technical field.

[0040] Polycarbonate 1, with a melt flow rate of 10 g / 10 min at 300℃ and 1.2 kg, a weight-average molecular weight of 24000, a water content of 0.3%, PC2100, Wanhua.

[0041] Polycarbonate 2, with a melt flow rate of 20 g / 10 min at 300℃ and 1.2 kg, a weight-average molecular weight of 20,000, a water content of 0.3%, PC2220, Wanhua.

[0042] Polycarbonate 1-1 is obtained by drying polycarbonate 1 at 120°C with a blower for 4 hours. The water content of the dried polycarbonate is 0.02%.

[0043] Polycarbonate 1-2 is obtained by drying polycarbonate 1 at 100°C using a blower for 4 hours. The water content of the dried polycarbonate is 0.1%.

[0044] Polycarbonate 2-1 is obtained by drying polycarbonate 2 at 120°C with a blower for 4 hours. The water content of the dried polycarbonate is 0.02%.

[0045] Polycarbonate 3-1 was obtained by drying polycarbonate 3 at 120℃ with a blower for 4 hours, resulting in a water content of 0.02%. The polycarbonate 3, at 300℃ and 1.2 kg, had a melt flow rate of 60 g / 10 min, a weight-average molecular weight of 13000, a water content of 0.2%, and was manufactured by Wanhua (PC2600).

[0046] Polyphenyl sulfone resin 1, with a melt flow rate of 35 g / 10 min at 356℃ and 10 kg, a weight-average molecular weight of 40,000, and a water content of 0.5%, G-KFSU11B, Zhuhai Wantong Special Plastics.

[0047] Polyphenyl sulfone resin 2, with a melt flow rate of 20 g / 10 min at 356℃ and 10 kg, a weight-average molecular weight of 59,000, and a water content of 0.5%, G-KFSU10B, Zhuhai Wantong Special Plastics.

[0048] Polyphenyl sulfone resin 3, with a melt flow rate of 50 g / 10 min at 356℃ and 10 kg, a weight-average molecular weight of 20,000, and a water content of 0.6%, G-KFSU15B, Zhuhai Wantong Special Plastics.

[0049] Polyphenylsulfone resin 1-1 is obtained by drying polyphenylsulfone resin 1 at 180℃ using a blower for 6 hours. The water content of the dried polyphenylsulfone resin is 0.05%.

[0050] Polyphenylsulfone resin 1-2 is obtained by drying polyphenylsulfone resin 1 at 160℃ using a blower for 4 hours. The water content of the dried polyphenylsulfone resin is 0.25%.

[0051] Polyphenylsulfone resin 2-1 is obtained by drying polyphenylsulfone resin 2 at 180℃ using a blower for 4 hours. The moisture content of the dried polyphenylsulfone resin is 0.1%.

[0052] Polyphenylsulfone resin 3-1 is obtained by drying polyphenylsulfone resin 3 at 180℃ using a blower for 4 hours. The moisture content of the dried polyphenylsulfone resin is 0.15%.

[0053] Antioxidant 1, Phosphite antioxidant, bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, melting point 234℃, RIANOX 686, Tianjin Lialong.

[0054] Antioxidant 2, phosphite antioxidant, tris(2,4-di-tert-butyl)phosphite, melting point 185℃, SONOX168, Mitutoyo Chemical.

[0055] Antioxidant 3, hindered phenolic antioxidant, bis(3,5-di-tert-butyl-4-hydroxyphenylpropionyl)hydrazine, melting point 230℃, RIANOX MD-1024, Tianjin Lialong.

[0056] Lubricant 1, pentaerythritol stearate, thermal decomposition temperature 330°C, PETS-AP, Italian FARK Pte Ltd.

[0057] Lubricant 2, oxidized polyethylene wax, thermal decomposition temperature 300℃, PED 521, Clariant, Germany.

[0058] Lubricant 3, Ethylene bis-stearamide, thermal decomposition temperature 260℃, ACRAWAX C Powdered, Lonza, USA.

[0059] Unless otherwise specified, all components used in the parallel embodiments and comparative examples are the same commercially available products.

[0060] Examples 1-11 A polycarbonate composition is prepared according to the formula weight parts in Table 1-2 and the preparation method including the following steps: according to the weight parts described in Table 1-2, each raw material is dried and then placed in an aluminum foil bag for sealing and storage. In specific preparation, after the raw materials are mixed evenly, they are melt-extruded by a twin-screw extruder (length-to-diameter ratio of 48:1) (320℃, 300 r / min, 50 kg / h) to prepare the polycarbonate composition.

[0061] In Tables 1 to 3, the total moisture content refers to the overall moisture content of the raw materials, polycarbonate resin and polyphenylene sulfone resin, at the time of feeding. The amounts of antioxidants and lubricants added are small, and their moisture content has a negligible impact on the overall moisture content of the raw materials.

[0062] Table 1

[0063] Table 2

[0064] Comparative Examples 1-7 The weight proportions of raw materials used in the following comparative examples are shown in Table 3. The preparation method is the same as that in Example 1 above.

[0065] Table 3

[0066] Test case The polycarbonate compositions obtained in the above examples and comparative examples were tested as follows.

[0067] (1) Tensile strength: Tested according to standard ASTM D638, with a tensile rate of 50 mm / min; (2) Notched impact strength (J / m): Tested using standard ASTM D256; (3) Heat distortion temperature (°C): The heat distortion temperature under a 1.82 MPa load was tested using the standard ASTM D648. (4) Solvent resistance (%): Tensile specimens described in ASTM D638 were used. The specimens were fixed in a fixture with a strain rate of 1.0%. A chemical reagent (Jinlongyu cooking oil) was evenly applied to the surface of the specimens. The specimens were wrapped with plastic wrap to prevent rapid evaporation of the chemical reagent. The specimens were placed under constant temperature and humidity conditions (23℃ / 50%RH) for 168 hours. The surface condition of the specimens was observed, and the tensile strength after solvent treatment was tested. The tensile strength retention rate was calculated. Tensile strength retention rate (%) = Tensile strength after solvent treatment / Initial tensile strength × 100%.

[0068] Tables 4 and 5 show the test data for the polycarbonate compositions prepared in the examples and comparative examples, respectively.

[0069] Table 4

[0070] Table 5

[0071] As shown in Tables 4 and 5 above, the polycarbonate composition provided by the present invention exhibits excellent notched impact strength, heat distortion temperature, and solvent resistance. Specifically, the notched impact strength is ≥680 J / m, the heat distortion temperature is ≥129℃, and the solvent resistance is ≥73%; more preferably, the notched impact strength is ≥724 J / m, and the solvent resistance is ≥80%; even more preferably, the notched impact strength is ≥746 ​​J / m, the heat distortion temperature is ≥145℃, and the solvent resistance is ≥90%.

[0072] As can be seen from Examples 1, 3 and 4, the polycarbonate composition prepared by each raw material component in a specific proportion has better notched impact strength, heat distortion temperature and solvent resistance.

[0073] As can be seen from Examples 1, 6 and 9, the larger the molecular weight of the polycarbonate resin or polyphenylene sulfone resin, the better the notched impact strength and solvent resistance of the polycarbonate composition prepared.

[0074] As can be seen from Examples 1 and 10, the higher the melting point of phosphite antioxidants, the better the notched impact strength and solvent resistance of the polycarbonate composition prepared.

[0075] As can be seen from Examples 1 and Comparative Examples 1-5, a high total water content or a low weight-average molecular weight of polycarbonate resin makes it difficult to achieve the technical effects of the present invention.

[0076] As can be seen from Example 1 and Comparative Example 6, the technical effects of the present invention can only be achieved when phosphite antioxidants are used in the polycarbonate system.

[0077] As can be seen from Example 1 and Comparative Example 7, when the thermal decomposition temperature of the lubricant in the polycarbonate system is low, it is difficult to achieve the technical effect of the present invention.

[0078] The foregoing examples are merely illustrative, used to explain some features of the method described in this invention. The appended claims are intended to claim the broadest possible scope, and the embodiments presented herein are demonstrated by the applicant's actual experimental results. Therefore, the applicant intends that the appended claims are not limited by the selection of examples illustrating the features of the invention. Some numerical ranges used in the claims also include sub-ranges within them, and variations within these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. A polycarbonate composition, characterized in that, By weight, it comprises the following components: 44-76 parts of polycarbonate resin, 24-56 parts of polyphenyl sulfone resin, 0.1-1 parts of antioxidant, and 0.1-1 parts of lubricant; The weight-average molecular weight of the polycarbonate resin is 15,000-55,000; The total water content of the polycarbonate resin and polyphenylene sulfone resin used in the preparation of the polycarbonate composition is ≤0.1%; The antioxidant is a phosphite antioxidant; The thermal decomposition temperature of the lubricant is ≥280℃; The lubricant is selected from at least one of pentaerythritol ester lubricants and oxidized polyethylene wax.

2. The polycarbonate composition according to claim 1, characterized in that, The phosphite antioxidant is selected from at least one of bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, and 3,9-bis(2,4-dicumylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosspiro[5.5]undecane.

3. The polycarbonate composition according to claim 1, characterized in that, The melting point of the phosphite antioxidant is ≥200℃; and / or The thermal decomposition temperature of the lubricant is 290-350℃.

4. The polycarbonate composition according to claim 3, characterized in that, The melting point of the phosphite antioxidant is 225-250℃.

5. The polycarbonate composition according to claim 1, characterized in that, The polyphenylene sulfone resin has a weight-average molecular weight of 18,000-60,000; and / or The polyphenylene sulfone resin has a melt flow rate of 20-50 g / 10 min at 365°C and 10 kg.

6. The polycarbonate composition according to claim 1, characterized in that, The polycarbonate resin is a bisphenol A type polycarbonate resin; and / or The polycarbonate resin has a weight-average molecular weight of 20,000-30,000; and / or The polycarbonate resin has a melt flow rate of 3-40 g / 10 min at 300°C and 1.2 kg.

7. The polycarbonate composition according to claim 1, characterized in that, The water content of the polycarbonate resin is ≤0.1%; and / or The water content of the polyphenylene sulfone resin is ≤0.25%.

8. A method for preparing the polycarbonate composition according to any one of claims 1-7, characterized in that, The components are mixed evenly and then melt-extruded to obtain the polycarbonate composition.

9. The use of the polycarbonate composition according to any one of claims 1-7 in the fields of household appliances, consumer electronics, and medical devices.

10. A kitchen appliance or electrical product, characterized in that, It is prepared using the polycarbonate composition according to any one of claims 1-7.

Citation Information

Patent Citations

  • TLCP modified polyphenylene sulfone / polycarbonate composite material and preparation method thereof

    CN113462160A

  • Polycarbonate composition as well as preparation method and application thereof

    CN119931301A